Optimal Quantity of Nano-Silicon for Electrospun Silicon/Carbon Fibers as High Capacity Anodes - Wang, Renheng; Sun, Yiling; Xiong, Keyu; Zheng, Junchao; Qian, Zhengfang; He, Zhenjiang (Frontiers in Chemistry, 2020)
In this study, silicon/carbon composite nanofibers (Si@CNFs) were prepared as electrode materials for lithium-ion batteries via a simple electrospinning method and then subjected to heat treatment. The morphology and structure of these materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The results show that the structure provides good electrical conductivity and affords sufficient space to accommodate volume expansion during charging/discharging. Furtherly, electrochemical performance tests show that the optimized Si@CNFs have an initial reversible capacity of 1,820 mAh g−1 at a current density of 400 mA g−1 and capacity retention of 80.7% after 100 cycles at a current density of 800 mA g−1. Interestingly, the optimized Si@CNFs have a superior capacity of 1,000 mAh g−1 (400 mA g−1) than others, which is attributed to the carbon substrate nanofiber being able to accommodate the volume expansion of Si. The SEI resistance generated by the Si@CNFs samples is smaller than that of the Si nanoparticles, which confirms that SEI film generated from the Si@CNFs is much thinner than that from the Si nanoparticles. In addition, the connected carbon substrate nanofiber can form a fiber network to enhance the electronic conductivity.